PENDIDIKAN SENI SEBAGAI BASIS PENDIDIKAN KARAKTER MULTIKULTURALIS - Sutiyono Sutiyono (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Art Education as a Basis of Multicultural Character Education. Thisarticle discusses art education as a basis for multicultural character education inIndonesia. As a multicultural nation with a variety of cultural backgrounds,Indonesia has been faced with conflicts, violences, clashes, and riots resulting fromsuch differences. Education is deemed to be responsible for such problems and onecause of its failure to solve them is that it does not focus on character building.Character building is necessary in order for the students to appreciatemulticulturalism and it can be integrated into art education.Keywords: multiculturalism, character education, art education